Growth of Electronic Transactions vs. Decline of Cash Circulation (The International Journal for Scientific Research, 2024)
The study aimed to identify the main factors contributing to the increased adoption of electronic transactions, examine the impact of electronic transaction growth on the decline of cash usage, analyze the benefits and challenges associated with the shift towards electronic transactions, assess the role of governments and central banks in promoting this shift, and explore the expected future of financial operations as this trend continues. The study adopted the descriptive-analytical approach, which was deemed suitable for the nature of the study, utilizing a questionnaire tool. The study sample consisted of 180 individuals. The study concluded that technological innovations and developments in digital payment infrastructure significantly contribute to the increased adoption of electronic transactions, with a response average of 3.55, underscoring the importance of electronic payment reliance. Electronic transactions provide multiple benefits, such as security and speed, while the growth of electronic transactions noticeably reduces dependency on cash. Continued growth in electronic transactions is expected to lead to fundamental changes in financial systems, enhancing transparency and reducing tax evasion. Moreover, reliance on electronic payments contributes to improving the quality of life, and electronic payments enhance economic efficiency and reduce costs associated with cash. The study recommended enhancing digital infrastructure, raising awareness of the benefits of electronic payments, and encouraging digital transformation policies in the financial sector.
Keywords: Electronic Financial Transactions; Money in Circulation; Saudi Market; Central Banks